PWE-294 The significance of the rectal cancer regression grade (RCRG) in prognosis after neo-adjuvant chemoradiotherapy treatment of adenocarcinoma of the rectum. (22nd June 2015) - Humes, D; McGrane, J; Wheeler, J; Acheson, A; Walter, CJ
Abstract : Introduction: Complete pathological response is widely accepted to be an independent predictor for better prognosis after neo-adjuvant chemoradiotherapy treatment (NCRT) of locally-advanced adenocarcinoma of the rectum. 1 Less is known about the role of the Rectal Cancer Regression Grades (RCRGs) in predicting prognosis where partial tumour regression is seen. The aim of this study was to examine the relationship between RCRG and mortality in patients with locally-advanced adenocarcinoma of the rectum treated with NCRT. Method: A retrospective study of all patients treated with NCRT for locally-advanced rectal cancer between 2004–2009 in 3 UK centres was undertaken. Data was collected from oncology, radiology and laboratory databases as well as patient records. Differences in mortality rates were compared for patients within the 3 different RCRG groups using univariate and multivariate analysis. The multivariate analysis adjusted for the known confounders of age, sex and stage of disease at presentation. A subset analysis was performed on patients with partial tumour regression by excluding those patients with a complete pathological response. Results: Of 273 patients treated, 183 (67%) were male. Median follow up time was 3.60 years (2.58–4.99). Univariate analysis demonstrated an association between higher RCRGs and increased mortality with hazard ratios (HRs) for RCRG1:RCRG2 of 2.05 (95% CI 1.67–3.59) and RCRG1:RCRG3 of 3.25 (95% CI 1.82–5.82). This association persisted when multivariate analysis was performed, with HRs for mortality of RGRC1:RCRG2 2.12 (95% CI 1.20–3.74) and RCRG1:RCRG3 of 3.14 (95% CI 1.74–5.67). Fifty-five patients demonstrated a complete pathological response and were excluded from the analysis of patients with partial tumour regression. Of the remaining 218 patients, univariate analysis demonstrated a HR for mortality in RCRG1:RCRG2 of 1.40 (95% CI 0.77–2.56) and RCRG1:RCRG3 of 2.30 (95% CI 1.24–4.26). Multivariate analysis of mortality gave HRs of 1.52 (95% CI 0.82–2.81) and 2.38 (95% CI 1.27–4.45) respectively. Conclusion: This study demonstrated an association between higher rectal cancer regression grades and an increased risk of mortality. This association, although weakened, appeared to persist amongst the subset of rectal cancer patients who only demonstrated partial tumour regression following chemoradiation. Disclosure of interest: None Declared. Reference: Maas M, Nelemans PJ, Valentini V, et al . Long-term outcome in patients with a pathological complete response after chemoradiation for rectal cancer: a pooled analysis of individual patient data. Lancet Oncol. 2010;11:835–44